GROWTH AND BIOMETRIC RELATIONSHIP OF PEARL OYSTER PINCTADA FUCATA (GOULD) - Chellam, A (Indian Journal of Fisheries, 2011)
Observations on the growth of pearl oyster,Pinctadafucata (= P. vulgaris) of the Gulfof Mannar have been made b&sed on thespatfall (Herdman, 1903; Devanesen andChidambaram, 1956; Chacko, 1970) and theinitial size of transplantation to the farm(Chellam, 1978). Alagaraja (1962) hasfound out the lengthweight relationship ofthe pearl oysters cultured at the Krusadaifarm by Devanesan and Chidambaram (1956)in cages.